2012
DOI: 10.1080/15433714.2012.663667
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Translation Efforts in Child and Youth Mental Health: A Systematic Review

Abstract: The availability of knowledge translation strategies that have been empirically studied and proven useful is a critical prerequisite to narrowing the research-to-practice gap in child and youth mental health. Through this review the authors sought to determine the current state of scientific knowledge of the effectiveness of knowledge translation approaches in child and youth mental health by conducting a systematic review of the research evidence. The findings and quality of the 12 included studies are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
(47 reference statements)
2
29
0
Order By: Relevance
“…Findings from the study on knowledge platform work are congruent with those previously reported by policymakers, stakeholders, and researchers on evidence-informed policymaking (El-Jardali, Lavis, Ataya, Jamal, Ammar, & Raouf, 2012;Wallace, Byrne, & Clarke, 2012;LaRocca, Yost, Dobbins, Ciliska, & Butt, 2012;El-Jardali, Jamal, Ataya, Jaafar, Raouf, Matta, & et al 2011;Wallace, Nwosu, &Clarke, 2012;Scott, Albrecht, O'Leary, Ball, Hartling, Hofmeyer, & et al 2012;Barwick, Schachter, Bennett, McGowan, Ly, Wilson, & et al 2012). Gaps in research production in relation to priorities of MEC, as well as a lack of skills among research users to acquire, assess, adapt, and use research evidence, were reported to hinder the use of research evidence in policymaking.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Findings from the study on knowledge platform work are congruent with those previously reported by policymakers, stakeholders, and researchers on evidence-informed policymaking (El-Jardali, Lavis, Ataya, Jamal, Ammar, & Raouf, 2012;Wallace, Byrne, & Clarke, 2012;LaRocca, Yost, Dobbins, Ciliska, & Butt, 2012;El-Jardali, Jamal, Ataya, Jaafar, Raouf, Matta, & et al 2011;Wallace, Nwosu, &Clarke, 2012;Scott, Albrecht, O'Leary, Ball, Hartling, Hofmeyer, & et al 2012;Barwick, Schachter, Bennett, McGowan, Ly, Wilson, & et al 2012). Gaps in research production in relation to priorities of MEC, as well as a lack of skills among research users to acquire, assess, adapt, and use research evidence, were reported to hinder the use of research evidence in policymaking.…”
Section: Discussionsupporting
confidence: 75%
“…Similar results have been reported by El-Jardali et al (2011). There is little empirical evidence on effective KT approaches and how KT strategies can be tailored for different contexts and disciplines (Wallace, Nwosu, & Clarke, 2012;Scott et al, 2012;Barwick et al, 2012).…”
Section: Discussionsupporting
confidence: 71%
“…Despite the frequent use of training as a discrete implementation strategy (Barwick et al, 2012), results of studies that have evaluated training as the sole implementation strategy have been disappointing (see review by Beidas & Kendall, 2010). Typical training efforts include printed education materials and one-time didactic workshops and are better than no training in improving therapist knowledge, but have no significant effect on client outcomes (Beidas & Kendall, 2010; Farmer et al, 2008; Fixsen et al, 2005; Shafran et al, 2009) or therapist behavior (Hawkins & Sinha, 1998; Sholomskas et al, 2005).…”
mentioning
confidence: 99%
“…First, studies identified through four previous reviews of implementation strategies in mental health (Barwick et al 2012; Landsverk et al 2011; Novins et al 2013; Powell et al 2014) were compiled and unique RCTs that reported quantitative outcomes were downloaded for full-text review. Second, with the help of an electronic resources librarian, an electronic keyword search was conducted in PubMed and PsycINFO for implementation trials published in any year up to March 2015.…”
Section: Methodsmentioning
confidence: 99%